Effect of periodontal diseases on the development of infective endocarditis - Bielacz, Magdalena; Kosek-Hoehne, Karolina; Hoehne, Dominik; Pawlak, Szymon; Janda, Andrzej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
In developed countries, infective endocarditis is rare, but in spite of the progress taking place in the diagnosis and treatment, there is still high risk of mortality. According to epidemiological data there are 1.7-6.2 morbidity cases out of 100 thousand people, and it increases with age, while mortality, despite intensive antibiotic treatment. varies between 10-50%. Some heart diseases and clinical conditions predispose to IE, and tearing of the mucous membranes of the mouth, colonized by numerous bacterial flora – as a result of dental procedures performed – may cause penetration of pathogens into the circulatory system and, thus contribute to the development of IE. The risk of bacteremia tied with periodontal diseases and dental procedures is greater than in the case of surgical intervention on the mucous membranes of the genitourinary system and gastrointestinal tract. In blood cultures, of those mostly isolated pathogens there are streptococci, enterococci, coagulase negative staphylococci and Gram-negative bacteria from the group HACEK in the oral cavity. In order to minimize the incidence of infective endocarditis there were established recommendations for the use of antibiotic prophylaxis.